Advantages of bus stop skipping and holding control in reducing schedule deviation. Issue 1 (19th March 2021) - Zhang, Hu; Liang, Shidong; Zhao, Shuzhi; Shang, Qiang
Abstract : In general, buses do not always operate in accordance with the set schedule in the modern-day transit system, mainly due to the randomness of passenger demand and running times. The failure to run on schedule deteriorates the quality of transit services. This paper proposes a real-time hybrid control strategy that is designed to shorten the passenger's waiting time caused by large schedule deviations, which can improve quality of transit services. Schedule deviations of a bus route are evaluated in order to judge whether the hybrid control strategy should be implemented or not. The proposed strategy includes skipping and holding actions, which are intended to allow buses to serve stops with high demand. Besides, to ensure the accuracy of schedule deviations, the controlled bus is followed by a non-controlled bus that provides schedule deviation data. The selection of appropriate skipping stops can be determined by maximising the benefits of a hybrid control strategy. Meanwhile, the control strategy is tested on a bus route. The threshold for implementing the control strategy is determined. Tests in this study prove the validity of the control strategy.